Balinese Women's Role and Gender Gap in the Sustainable Tourism Development - Budi Shantika; Ni Made Ernawati; Ni Luh Ayu Kartika Yuniastari Sarja (International Journal of Green Tourism Research and Applications, 2021)
This study aims to determine women's role and involvement in the development of sustainable tourism in Bali and to know how Balinese women are the main drivers of cultural and environmental preservation in Bali. The study uses a qualitative method of literature review. The research stage was carried out by collecting literature sources, both primary and secondary. Balinese women have a vital role in the preservation of culture and the environment in Bali. It can be concluded that Balinese women are the drivers of sustainable tourism in several tourism sectors, such as culinary tourism, cultural tourism, and environmental conservation. Balinese women are pioneers in the development of culinary tourism, especially traditional culinary in Bali but are not given many chance to participate in development planning actively. Balinese women are still collided by the patriarchal hegemony in the local traditional culture.